2021
DOI: 10.1007/s11666-021-01239-2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Particle Properties in Plasma Spraying Based on Machine Learning

Abstract: Thermal spraying processes include complex nonlinear interdependencies among process parameters, in-flight particle properties and coating structure. Therefore, employing computer-aided methods is essential to quantify these complex relationships and subsequently enhance the process reproducibility. Typically, classic modeling approaches are pursued to understand these interactions. While these approaches are able to capture very complex systems, the increasingly sophisticated models have the drawback of requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…They have demonstrated that the trends of particle properties are estimated to be extremely faster than the averaged plasma jet simulation (from 3 h to less than 5 s). 242) By technological outcomes, this field is becoming a hot topic for controlling using the ML and AI techniques without physical understanding of the significant parameters. We emphasize the importance of understanding the physics of the system in order to achieve comprehensive control of critical parameters.…”
Section: Spray Coatingmentioning
confidence: 99%
“…They have demonstrated that the trends of particle properties are estimated to be extremely faster than the averaged plasma jet simulation (from 3 h to less than 5 s). 242) By technological outcomes, this field is becoming a hot topic for controlling using the ML and AI techniques without physical understanding of the significant parameters. We emphasize the importance of understanding the physics of the system in order to achieve comprehensive control of critical parameters.…”
Section: Spray Coatingmentioning
confidence: 99%
“…The goal is to establish a digital twin of the simulation process which significantly reduces the computation time while still sufficiently predicting the general behavior of the particles. An approach for training a ResNet similar to the one presented in the following and a comparison of ResNet results with results of a support vector machine can be found in [25]. Further ResNet results are also available in [37].…”
Section: Prediction Of the Plasma Spraying Coating Processmentioning
confidence: 99%
“…First, we study the prediction of specific cutting forces for different materials and compare the results with measurement data from, e.g., [22]. Second, the particle behavior in a plasma spraying coating process [23][24][25] is predicted based on large simulation data sets. These use cases stem from cooperations within the DFG project EXC-2023 "Internet of Production".…”
Section: Introductionmentioning
confidence: 99%
“…Note that even the choice d = 1 is possible and, in addition, that networks of this type have been already proved to satisfy different formulations of the universal approximation theorem [31][32][33]. Further, they have been also applied to several (realworld) training problems [34,35].…”
Section: Neural Differential Equations and Mean-field Limitmentioning
confidence: 99%